Opportunities to improve end-of-life communication and decision-making for seriously ill hospitalised patients and their families. Issue 2 (1st June 2012) - You, JJ; Heyland, DK; Dodek, P; Lamontagne, F; Barwich, D; Tayler, C; Porterfield, P; Simon, J; Enns, Bert
Abstract : In face-to-face interviews with seriously ill patients and/or their family members, we used a validated questionnaire to assess key components of in-hospital end-of-life (EOL) communication and decision-making at 11 Canadian hospitals. We report preliminary data from 123 seriously ill hospitalised patients (age 80±9 years, mean±SD) and 77 family members (age 62±13 years). Patients rated being comfortable and minimising suffering as 8.8±2.5 (1=not at all important; 10=very important) and avoidance of being attached to machines as 7.5±3.5. Nearly 50% of participants reported that a decision was made in hospital about the use of life-sustaining treatments (LST) in the event of a life-threatening deterioration. However, when patients were asked about EOL communication with their in-hospital care providers, only 8 (6.5%) reported receiving a disclosure of prognosis, 37 (30.1%) received information about comfort measures to control symptoms, 15 (12.2%) were asked what was important to them when considering decisions about EOL care, and 16 (13.0%) had discussed the risks and benefits of life-sustaining treatments (LST) with a physician. In family members who were asked about EOL communication regarding their relative (the patient), 12 (15.6%) received a disclosure of prognosis, 24 (31.2%) received information about comfort measures, 12 (15.6%) were asked what was important to them when considering decisions about EOL care for their relative, and 11 (14.3%) had discussed risks and benefits of LST with a physician. There are many opportunities to improve the quality of EOL communication and decision-making with seriously ill hospitalised patients and their families.